The creative thinking development of the technical university student - Valentina G. Ryndak; Alfiya V. Moskvina; Polina G. Labzina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The necessity of future engineers’ working with professional literature in foreign languages is mentioned in the article. The process mentioned above is performed by special pedagogical means and technologies. The solving of the problem of developing student’s discursive-creative abilities specifies an important role of cognitive tasks in the process of dealing with scientific discourse encouraging making up of personality which is ready for the future professional activity. The theoretical analysis lets us assume that such tasks are aimed at perception, understanding and creating students’ own discourse as the processes mentioned above require such mental operations as analysis, synthesis, comparison, generalization, specification, abstracting in the process of information decoding, deverbalization and explication that result in thinking flexibility, breadth, fluency and originality and lead to its creativity. The theoretical basis lets us use the humanitarian techniques contributing to the creative-thinking development. The program of the creative-thinking development is also presented in the article.